Optimizing water use efficiency and economic return of super high yield spring maize under drip irrigation and plastic mulching in arid areas of China - Liu, C. (2020)
The objectives of this study were to optimize irrigation water use, grain yield, WUE, and economic return of super high yield maize in a drip irrigation and plastic film mulch system in Xinjiang. Experiments were conducted in Qitia County, Xinjiang, and included four drip irrigation treatments: T1, 600 mm (CK); T2, 540 mm; T3, 480 mm; and T4, 420 mm. Six density-tolerant maize hybrids were planted in 2014 and 2015. Grain yield and economic return did not significantly change in response to a 10% decrease in irrigation level, whereas evapotranspiration decreased and WUE increased (4.61%–6.66%). High grain yield (15.7–19.1 Mg ha−1), WUE (2.47–2.77 kg m−3), and economic return (1691.6–2605.7 US$ ha−1) were achieved under the T2 treatment. The combined techniques of drip irrigation, plastic film mulching, and increased planting density improved yield. Taking into account grain yield, economic return, and ecological effects, an irrigation amount of 540 mm is optimal for drip irrigation–plastic film mulching systems in arid areas.